Physical Literacy Knowledge Questionnaire: feasibility, validity, and reliability for Canadian children aged 8 to 12 years - Longmuir, Patricia E; Woodruff, Sarah J; Boyer, Charles; Lloyd, Meghann; Tremblay, Mark S (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Physical literacy is defined as the motivation, confidence, physical competence, and knowledge and understanding to engage in physical activity for life. Physical literacy knowledge and understanding encompasses movement (how to move), performance (evaluation of movement), and health and fitness (value of exercise, need for relaxation and sleep, etc.). This paper describes the development and evaluation of a standardized assessment of physical literacy knowledge and understanding for Canadian children in grades 4, 5, and 6. Methods Proposed Physical Literacy Knowledge Questionnaire (PLKQ) content was identified through expert consultation and a review of provincial/territorial physical education curricula for grades 4 to 6. Open-ended questions verified language and generated response options. Feasibility was assessed via completion time and error frequency. Item validity assessed scores by age, gender, and teacher ratings of student knowledge. Test-retest reliability was assessed over short (2-day) and long (7-day) intervals. Results Subsets of 678 children (54% girls, 10.1 ± 1.0 years of age) completed the feasibility and validity assessments. Response errors (missing or duplicate responses, etc.) were minimal (2% or less) except for one question (7% error) about the use of safety gear during physical activity. A Delphi process among experts in children’s physical activity and fitness achieved consensus on the core content and supported an item analysis to finalize item selection. As expected, knowledge scores increased with age (partial eta2 = 0.07) but were not related to gender (p = 0.63). Teacher ratings of children’s knowledge of physical activity behaviour (r = 0.13, p = 0.01) and fitness (r = 0.12, p = 0.03), but not movement skill (r = 0.07, p = 0.19) were associated with PLKQ scores. Test-retest reliability for PLKQ score and individual questions was substantial to excellent for 71% of comparisons over a 2-day interval, but lower over a 7-day interval (53% substantial or excellent). Items with low reliability had high or low proportions of correct responses. Conclusions This study provides feasibility and validity evidence for the Physical Literacy Knowledge Questionnaire as an assessment of physical literacy knowledge for Canadian children in grades 4, 5, and 6. Completion rates were high and knowledge scores increased with age. Streamlining of the content in accordance with Delphi panel recommendations would further enhance feasibility, but would also focus the content on items with limited reliability. Future studies of alternative item wording and responses are recommended to enhance test-retest reliability.